A Case Report of a Patient with Advanced Acinar Cell Carcinoma of the Pancreas: Long-Term Survival with Regional, Systemic and Targeted Therapy. Issue 2 (March 2013) - Ang, Celina; Herran, Luis A; Lagunes, Diane Reidy; Klimstra, David S; Kemeny, Nancy E
Acinar cell carcinoma of the pancreas is an uncommon malignancy for which there are no prospective, randomized data to guide therapy. We describe the clinical course and management of a patient with advanced pancreatic acinar cell carcinoma who is alive seven years after diagnosis using systemic and regional chemotherapies as well as molecularly targeted agents.